Pendugaan Umur Simpan Fruit Leather Mangga dan Nanas menggunakan Metode ASLT Model Arrhenius - Fiana P. Haerunisa; Amila Khairina; Kelik Putranto (Ma'soem University, 2023)
The purpose of this study was to determine the shelf life of pineapple mango fruit leather during storage in three temperature conditions namely 25oC, 35oC and 45oC. The method of assessing storage life with ASLT is carried out under the influence of temperature to accelerate the development of reactions that result in decomposition. fruit leather was stored in three incubators at 25oC, 35oC and 45oC for 20 days. Observations were made on the pineapple mango fruit leather in each incubator every 5 days. The data obtained was processed using simple linear regression method. The results of calculations with the Arrhenius equation obtained a correlation coefficient (R2) for water content of 0.8333; Aw of 0.9116; texture of 0.9006; taste of 0.9739 and color of 0.8597. Flavor has the highest colleration coefficient selected as a determinant of the shelf life of pineapple mango fruit leather. Based on the results of calculations with the Accelerated Shelf Life Test (ASLT) method, it can be concluded that the shelf life of pineapple mango fruit leather at 25°C is 72 days (2 months 4 days); at 35°C is 43 days (1 month 13 days); and at 45°C is 32 days (1 month 2 days).